Effect of NaCl on physiological, biochemical, and ionic parameters of naked oat (Avena nuda L.) line Bayou1 - Liu, Liyun; Assaha, Dekoum V. M.; Islam, Mohammad Sohidul; Rajendran, Karthika; Theivasigamani, Parthasarathi; Soufan, Walid; Ayman, El Sabagh; Ueda, Akihiro (Frontiers in Sustainable Food Systems, 2024)
Studying salinity tolerant mechanisms of oats could assist breeders in increasing oat production and their economic income in salt-affected areas, as the total amount of saline land in the world is still increasing. The present study was carried out to better understand the salt tolerance mechanism of the naked oat line Bayou1. A soil experiment was conducted on seventeen-day-old Bayou1 seedlings treated with varying concentrations of NaCl for a period of 12 days. Bayou1 plants grew optimally when treated with 50 mM NaCl, demonstrating their salinity tolerance. Reduced water uptake, decreased Ca 2+ , Mg 2+ , K + , and guaiacol peroxidase activity, as well as increased Na + concentration in leaves, all contributed to a reduction in shoot reduced Deleted[karthika rajendran]: This is a provisional file, not the final typeset article growth. However, the damage to ionic homeostasis caused by increased Na + concentrations and decreased K + concentrations in the roots of Bayou1 did not inhibit its root growth, indicating that the main salt-tolerant mechanism in Bayou1 existed in its roots. Further, a hydroponic experiment found that increasing Na + concentration in root cell sap enhanced root growth, while maintaining the integrity of root cell membranes. The accumulated Na + may have facilitated the root growth of Bayou1 exposed to NaCl by effectively adjusting cellular osmotic potential, thereby ensuring root cell turgor and expansion. (GPX) Deleted[karthika rajendran]: ing Deleted[karthika rajendran]: from Deleted[karthika rajendran]: s Deleted[karthika rajendran]: an increasing amount of Deleted[karthika rajendran]: are associated with Deleted[karthika rajendran]: reduced Deleted[karthika rajendran]: resistance Deleted[karthika rajendran]: . Deleted[karthika rajendran]: However, abiotic stresses, including drought and salinity, directly inhibits the growth of naked oats and restricts effective utilization and development of the cereal Deleted[karthika rajendran]: For instance Deleted[karthika rajendran]: decreased Deleted[karthika rajendran]: homeostasis Deleted[karthika rajendran]: along Deleted[karthika rajendran]: with Deleted[karthika rajendran]: T Deleted[karthika rajendran]: iciently cope with and Deleted[karthika rajendran]: under Deleted[karthika rajendran]: conditions by maintaining ion Deleted[karthika rajendran]: Various plant organs, including Deleted[karthika rajendran]: exhibits Deleted[karthika rajendran]: capacity Deleted[karthika rajendran]: demonstrates Deleted[karthika rajendran]: nt capacity Deleted[karthika rajendran]: t Deleted[karthika rajendran]: through Deleted[karthika rajendran]: